Digital Comics as a Medium for Instilling Character Values: A Speech Act Study on “Pak Guru Inyong” - Imaduddin, Fauzan Nur; Azizah, Ririn Nurul (The Future of Education Journal, 2025)
This article aims to analyze the forms and types of speech acts in the digital comic Pak Guru Inyong and how its language strategies effectively internalize character values in readers. The study employs a descriptive qualitative approach using pragmatic discourse analysis, applying Searle’s speech act theory consists of locutionary, illocutionary, and perlocutionary acts. Data were drawn from the comic’s dialogue and visual elements that reflect values such as responsibility, religiosity, hard work, and empathy. The findings reveal that illocutionary acts, especially expressive, assertive, and directive types dominate in delivering educational messages in subtle yet impactful ways. The combination of visual and linguistic strategies successfully shapes readers’ character awareness through humor, reflection, and grounded social critique. This study confirms that comics can serve as communicative, meaningful, and engaging alternative learning media to support character education in the digital age.